Irrigation Inequalities in Pakistan 1960-1980: A District-level Analysis (The Pakistan Development Review, 1994)
This study estimates the magnitudes of inequality in the distribution of irrigated areas at three points in time and extends the fmdings of Gill and Sampath (1990) using more disaggregated data. Specifically, it provides estimates of the level of inequality in the distribution of land and irrigation-related attributes among agricultural households across farm-size groups at provincial and district levels. It decomposes the levels of inequality in each province in terms of its two major components, namely, "betweendistricts" and "within-district" inequality, and tests a modified "Kuznet" hypothesis, according to which the relationship between the levels of inequality and the levels of development is an inverted "U". The major findings of the study are: There exists considerable inequality in the distribution of various land area variables across farm-size groups in all the districts of Pakistan, with considerable inter-district variations in their levels and movements over time; between the "within-district" inequality and "betweendistricts" ineqUality. The former represents 91 percent, 76 percent, 75 percent, and 65 percent of total inequalities for Sindh, the Punjab, Balochistan, and the NWFP, respectively. This means that more has to be done in terms of the irrigation distribution policy than in terms of removing the inter-district variations in irrigation development. And, finally, the modified "Kuznet" hypothesis is valid in explaining the inter-district variations in the levels of inequality in the distribution of at least some of the land area variables.